2014
DOI: 10.1186/1471-2458-14-232
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-utilization of child immunization in Pakistan: evidence from the Demographic and Health Survey 2006-07

Abstract: BackgroundThe proportion of incompletely immunized children in Pakistan varies from 37-58%, and this has recently resulted in outbreaks of measles and polio. The aim of this paper is to determine the factors associated with incomplete immunization among children aged 12-23 months in Pakistan.MethodsSecondary analysis was conducted on nationally representative cross-sectional survey data from the Pakistan Demographic and Health Survey, 2006-07. The analysis was limited to ever-married mothers who had delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
103
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 17 publications
14
103
2
3
Order By: Relevance
“…Culturally the father is considered the bread winner and is expected to provide for the financial needs of the family. Relating to this Bugvi et al [25] working in Pakistan declared in their study that maternal occupation did significantly affect immunization coverage of children in the general population. A poor unskilled mother is unlikely to immunize her child.…”
Section: Association Between Occupation Of Parents and Children Immunizmentioning
confidence: 75%
“…Culturally the father is considered the bread winner and is expected to provide for the financial needs of the family. Relating to this Bugvi et al [25] working in Pakistan declared in their study that maternal occupation did significantly affect immunization coverage of children in the general population. A poor unskilled mother is unlikely to immunize her child.…”
Section: Association Between Occupation Of Parents and Children Immunizmentioning
confidence: 75%
“…Detailed analysis of coverage reports submitted at sub-district and district level offices is not routinely conducted, with few districts reporting vaccine coverage exceeding 100% (17,18) Low vaccine demand also accounts for declining rates of completed vaccination among children. Vaccine demand is correlated with parental knowledge of vaccine importance, parental education and socioeconomic status (43,47,48). Published data indicate that higher maternal education is positively associated with vaccine uptake (4,10,14,22).…”
Section: Quality Of Vaccination Servicesmentioning
confidence: 99%
“…It has been widely established that "belief in the goodness of vaccination" is considerably more important for motivating caregivers than scientific knowledge about vaccines (14,22,48,(52)(53)(54). Mothers unaware of vaccine side-effects were more likely to have their children vaccinated (22) and, paradoxically, fear of common side-effects was linked to vaccine refusal (14,22), indicating the importance of proper counselling of caregivers before and after vaccinating a child.…”
Section: Quality Of Vaccination Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results have shown that children born in the hospital are more likely to be immunized as compare to those who were born at home. It explains the complementary effect of place of delivery of the child and its immunization (Bugvi et al, 2014). …”
Section: Resultsmentioning
confidence: 99%